Intermittent Fasting Protects against Alzheimer’s Disease Possible through Restoring Aquaporin-4 Polarity - Zhang, Jingzhu; Zhan, Zhipeng; Li, Xinhui; Xing, Aiping; Jiang, Congmin; Chen, Yanqiu; Shi, Wanying; An, Li (Frontiers in Molecular Neuroscience, 2017)
The impairment of amyloid-β (Aβ) clearance in the brain plays a causative role in Alzheimer’s disease (AD). Polarity distribution of aquaporin-4 (AQP4) is important to remove Aβ from brain. AQP4 polarity can be influenced by the ratio of two AQP4 isoforms M1 and M23 (AQP4-M1/M23), however, it is unknown whether the ratio of AQP4-M1/M23 changes in AD. Histone deacetylase 3 has been reported to be significantly increased in AD brain. Moreover, evidence indicated that microRNA-130a (miR-130a) possibly mediates the regulation of histone deacetylase 3 on AQP4-M1/M23 ratio by repressing the transcriptional activity of AQP4-M1 in AD. This study aimed to investigate whether intermittent fasting (IF), increasing the level of an endogenous histone deacetylases inhibitor β-hydroxybutyrate, restores AQP4 polarity via miR-130a mediated reduction of AQP4-M1/M23 ratio in protection against AD. The results showed that IF ameliorated cognitive dysfunction, prevented brain from Aβ deposition, and restored the AQP4 polarity in a mouse model of AD (APP/PS1 double-transgenic mice). Additionally, IF down-regulated the expression of AQP4-M1 and histone deacetylase 3, reduced AQP4-M1/M23 ratio, and increased miR-130a expression in the cerebral cortex of APP/PS1 mice. In vitro, β-hydroxybutyrate was found to down-regulate the expression of AQP4-M1 and histone deacetylase 3, reduce AQP4-M1/M23 ratio, and increase AQP4-M23 and miR-130a expression in 2 μM Aβ-treated U251 cells. Interestingly, on the contrary to the result observed in 2 μM Aβ-treated cells, AQP4 expression was obviously decreased in cells exposed to 10 μM Aβ. miR-130a mimic decreased the expression of AQP4-M1 and the ratio of AQP4-M1/M23, as well as silencing histone deacetylase 3 caused the up-regulation of AQP4 and miR-130a, and the reduction of AQP4-M1/M23 ratio in U251 cells. In conclusion, IF exhibits beneficial effects against AD. The mechanism may be associated with recovery of AQP4 polarity, resulting from the reduction of AQP4-M1/M23 ratio. Furthermore, β-hydroxybutyrate may partly mediate the effect of IF on the reduction of AQP4-M1/M23 ratio in AD, in which miR-130a and histone deacetylase 3 may be implicated.